The Production of Protein-Rich Poultry Fodder by Liquid Fermentation of the Accumulated Remains of Marine Organisms on Seashore (Latakia University Journal -Biological Sciences Series, 2013)
The accumulated remains of marine organisms on sea shores are considered crude materials high in their nutritional values. The remains for medculture media for fermentation whichwas utilizedin this study to obtain biomass rich in protein by usingstrains of micro- organism sisolated from natural sources such as Saccharomyces cerevisiae and Asper gillusniger. This is done after 2% sulfuric acidhydrolysisandafter deciding theoptimum conditions forthe fermentation process.Theresults showed that the amount of protein contentis directly proportionalto the duration of incubation untilthe fifteenth day, whenthe highest proteincontentwas28.52%of dry matter for the culture of the fungus A.niger comparedto3.44% prote in content of dry matter in the rawmaterial. A fodder mixture was then applied to groups of poultry, whereprotein source (soybean) incommercial fodder wascompletely replaced with the resulting biomass.The daily growth average was 18.70g and the feed conversion was 2.05 for the studied chicks of ages ranging between 3-16 days.